Virtual education during COVID-19 in higher education: A systematic review - Fatima del Socorro Torres-Caceres; Juan Méndez-Vergaray; Edith Gissela Rivera-Arellano; Mildred Jénica Ledesma-Cuadros; Yolanda Josefina Huayta-Franco; Edward Flores (Universidad de Deusto, 2022)
The objective of the present systematic review aimed to analyze studies linked to online teaching-learning, digital competence tutoring, and technological tools in virtual education during COVID-19 in higher education. The suggested methodology by the PRISMA declaration was pursued; the information search was conducted in Scopus, EBSCO, Springer Open, ProQuest, and One File. The target period ranged from May 10, 2021, to July 4, 2021; the identification, screening, eligibility, and inclusion for its progress were performed. The search produced a total of 230 studies, with 45 remaining. The inclusion criteria included original peer-reviewed research articles and qualitative and quantitative studies in higher education, comprising teachers and students addressing the study objective. In contrast, the exclusion criteria covered bibliographic reviews with procedural deficiencies, studies not exposed to a peer review process, and those not depicting a relationship with parts of the study. The results reveal that online teaching-learning, digital competence tutoring, and technological tools have been affirmative features expected to persist in higher virtual education engendered by the COVID-19 pandemic. Received: 5 October 2021 Accepted: 22 April 2022